No evidence of neuronal damage as measured by neurofilament light chain in a HIV cure study utilising a kick-and-kill approach - Jasmini Alagaratnam; Wolfgang Stöhr; Jamie Toombs; Amanda Heslegrave; Henrik Zetterberg; Magnus Gisslén; Sarah Pett; Mark Nelson; Amanda Clarke; Nneka Nwokolo; Margaret A. Johnson; Maryam Khan; et al. (Elsevier, 2021)
Objective: HIV-remission strategies including kick-and-kill could induce viral transcription and immune-activation in the central nervous system, potentially causing neuronal injury. We investigated the impact of kick-and-kill on plasma neurofilament light (NfL), a marker of neuro-axonal injury, in RIVER trial participants commencing antiretroviral treatment (ART) during primary infection and randomly allocated to ART-alone or kick-and-kill (ART + vaccination + vorinostat (ART + V + V)). Design: Sub-study measuring serial plasma NfL concentrations. Methods: Plasma NfL (using Simoa digital immunoassay), plasma HIV-1 RNA (using single-copy assay) and total HIV-1 DNA (using quantitative polymerase chain reaction in peripheral CD4+ T-cells) were measured at randomisation (following ≥22 weeks ART), week 12 (on final intervention day in ART + V + V) and week 18 post-randomisation. HIV-specific T-cells were quantified by intracellular cytokine staining at randomisation and week 12. Differences in plasma NfL longitudinally and by study arm were analysed using mixed models and Student's t-test. Associations with plasma NfL were assessed using linear regression and rank statistics. Results: At randomisation, 58 male participants had median age 32 years and CD4+ count 696 cells/μL. No significant difference in plasma NfL was seen longitudinally and by study arm, with median plasma NfL (pg/mL) in ART-only vs ART + V + V: 7.4 vs 6.4, p = 0.16 (randomisation), 8.0 vs 6.9, p = 0.22 (week 12) and 7.1 vs 6.8, p = 0.74 (week 18). Plasma NfL did not significantly correlate with plasma HIV-1 RNA and total HIV-1 DNA concentration in peripheral CD4+ T-cells at any timepoint. While higher HIV-specific T-cell responses were seen at week 12 in ART + V + V, there were no significant correlations with plasma NfL. In multivariate analysis, higher plasma NfL was associated with older age, higher CD8+ count and lower body mass index. Conclusions: Despite evidence of vaccine-induced HIV-specific T-cell responses, we observed no evidence of increased neuro-axonal injury using plasma NfL as a biomarker up to 18 weeks following kick-and-kill, compared with ART-only.